Peran Hukum Adat dalam Penanggulangan Bencana Gempa Bumi dan Tsunami Aceh - Taqwaddin Husin; Teuku Alvisyahrin (Kanun Jurnal Ilmu Hukum, 2014)
In the wake of earthquake and tsunami in Aceh, Indonesia, Desember 26th 2004, it caused almost all village governance. It is the lawest structure of governance based on customary law. Its community may apply the law to manage their community relationship and also in running the governance. In Acehnese customary law, the common interest must be privilege than personal one. Working together is a main principle based on the law. In emergency time, it was famous among victims of the disaster. The helped each other to fins the lasing, families efforts of recovery and the governance empowerment is priority. The Role of Customary Law in Preventing Earthquake and Tsunami in Aceh